Antioxidant Properties of Artemisia annua Extracts in Model Food Emulsions - Monika Skowyra; Maria Gabriela Gallego; Francisco Segovia; Maria Pilar Almajano (MDPI AG, 2014)
Artemisia annua is currently the only commercial source of the sesquiterpene lactone artemisinin. Although artemisinin is a major bioactive component present in this Chinese herb, leaf flavonoids have shown a variety of biological activities. The polyphenolic profile of extract from leaves of A. annua was assessed as a source of natural antioxidants. Total phenolic content and total flavonoid content were established and three assays were used to measure the antioxidant capacity of the plant extract. The measurement of scavenging capacity against the 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation, the oxygen radical absorbance capacity (ORAC) and the ferric reducing antioxidant power (FRAP) were 314.99 µM Trolox equivalents (TE)/g DW, 736.26 µM TE/g DW and 212.18 µM TE/g DW, respectively. A. annua extracts also showed good antioxidant properties in 10% sunflower oil-in-water emulsions during prolonged storage (45 days) at 32 °C. Artemisia extract at 2 g/L was as effective as butylated hydroxyanisole (BHA) at 0.02 g/L in slowing down the formation of hydroperoxides as measured by peroxide value and thiobarbituric acid reactive substances. The results of this study indicate that extract of A. annua may be suitable for use in the food matrix as substitutes for synthetic antioxidants.